Živo-mrtvo telo v dramatiki Simone Semenič - Murnik, Maja (Amfiteater (Ljubljana), 2019)
The article explores the theme of the corpse or the living-dead body in the dramatic writing of Simona Semenič. Existing discussions of her oeuvre do not thematise the body but instead focus on the disintegration of dramatic form and on the formal innovation in this "no longer dramatic writing" (Poschmann) as well as on ethical questions. The article begins with a brief overview of the research made thus far, focusing especially on how the author brings attention to the materiality and corporeality of the texts themselves. The coexistence of different temporal-spatial layers of action, images, scenes and discourses characteristic for Semenič's work, which corresponds with the hybrid experience of the modern world in the present-day augmented reality as well as mixed reality, is also pointed out. The bulk of the article is devoted to the analysis of the function and role of the living-dead body in Semenič's dramatic texts. Although the author does not use the term "livingdead body", the syntagm can be useful due to its duality: Semenič's corpses are namely not mere dead bodies but, paradoxically, express a certain liveness precisely because they are written off, cancelled and dead. They have to be understood as transitional and passing bodies that occupy the liminal space on the edge between life and death. The article continues with the interpretation of their meaning and function in several of Semenič's dramatic texts, ascertaining that the living-dead body is a metaphor for dramatic action - although this body is in a certain sense excluded from the text, it also stands for its deepest truth, which, as a rule, the dramatic characters are incapable of understanding. But it is also the metaphor for the broader state of society, as seen by the author. In certain texts (e.g., 1981 and we, the european corpses), living-dead bodies function as corpses-witnesses and are adopted as a symbol of shattered dreams for a better life and a more just and equal society. On the other hand, Semenič's living-dead bodies also point to the fundamental structure of the workings of biopolitical power. Agamben's concept of homo sacer, a person without any value, who can be killed without punishment but cannot be sacrificed, is therefore introduced. The play the feast or the story of a savoury corpse or how roman abramovič, the character janša, julia kristeva, age 24, simona semenič and the initials z.i. found themselves in a tiny cloud of tobacco smoke (the interpretation of which is quite extensive) presents this kind of homines sacri, appearing as incarnations of a corpse, which is made into a stew that the eminent guests feast upon. The corpse represents the bleak destinies of abused and killed women from the Balkans and the Middle East, giving them a voice and, by relating their stories, restoring their human dignity. In this play, Semenič thus points to the structure of society that constitutes bios through ingesting the nameless and lawless zoe. The disciplining of resistant bodies can also be seen in the play seven cooks, four soldiers and three sophias, which enacts the very essence of how society functions. The workings of social structures are unmasked also in the author's autobiographical solo performances in the victim trilogy, in which the resistant body is her own.
Keywords: biopolitics; biopolitična oblast; corpse; homo sacer; living-dead body; resistant bodies; Semenič, Simona; truplo; uparna telesa; živo-mrtvo telo